2008
DOI: 10.1139/g08-083
|View full text |Cite
|
Sign up to set email alerts
|

Association mapping of yellow pigment in an elite collection of durum wheat cultivars and breeding lines

Abstract: Association mapping (AM) is an alternative or complementary strategy to QTL mapping for describing associations between genotype and phenotype based on linkage disequilibrium (LD). Yellow pigment (YP), an important end-use quality trait in durum wheat (Triticum turgidum L. var. durum), was evaluated to determine the ability of AM to identify previously published QTL and to identify genomic regions for further genetic dissection. The YP concentration was determined for 93 durum wheat accessions sampled from a v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
38
2
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 45 publications
(45 citation statements)
references
References 33 publications
4
38
2
1
Order By: Relevance
“…Thus, the percentages of explained vari-the nine Chilean durum wheat genotypes studied exhibited the same PCR banding pattern with both the PSY1Al and PSY1Ba alleles (Figure 3 and 4), which are associated with intermediate (Singh et al, 2009) and low levels of GYPC (Reimer et al, 2008;, respectively, in agreement with the phenotypic results previously reported (Figure 1). …”
Section: Figuresupporting
confidence: 89%
See 3 more Smart Citations
“…Thus, the percentages of explained vari-the nine Chilean durum wheat genotypes studied exhibited the same PCR banding pattern with both the PSY1Al and PSY1Ba alleles (Figure 3 and 4), which are associated with intermediate (Singh et al, 2009) and low levels of GYPC (Reimer et al, 2008;, respectively, in agreement with the phenotypic results previously reported (Figure 1). …”
Section: Figuresupporting
confidence: 89%
“…The effect of the PSY1D locus on the yellowness of the endosperm has been less well studied, but recent evidence shows that it also significantly influences this trait (Ravel et al, 2013). However, the percentages of endosperm yellowness or GYPC variability explained by the PSY1 loci are not reported in several studies (Pozniak et al, 2007, Reimer et al, 2008Dubcovsky, 2008, He et al, 2009a;He et al 2009b;Singh et al, 2009). Therefore, those values previously mentioned are only a partial sample of all cases in which the homeologous PSY1 loci have been studied so far (Schulthess, 2013).…”
Section: Figurementioning
confidence: 99%
See 2 more Smart Citations
“…Significant marker-trait associations for YPC have been detected on all of the chromosomes by linkage mapping (Parker et al 1998;Hessler et al 2002;Pozniak et al 2007;Patil et al 2008;Zhang et al , 2009Howitt et al 2009;Blanco et al 2011;Roncallo et al 2012) and by association mapping (Reimer et al 2008).…”
Section: Genetic Control Of Carotenoid Biosynthesismentioning
confidence: 99%